2006
DOI: 10.1111/j.1574-6941.1995.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Algal growth enhancement by bacteria: Is consumption of photosynthetic oxygen involved?

Abstract: Pseudomonas diminuta and P. vesicularis, two obligate aerobes isolated from laboratory algal cultures, stimulated the growth of the green microalgae Scenedesmus bicellularis and Chlorella sp., without releasing any growth promoting substance. An intimate contact between both microorganisms was necessary for significant algal growth enhancement. The possibility of algal growth stimulation by bacterial attenuation of photosynthetic oxygen tension was indirectly examined by simulating the effect of bacteria throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The elucidation of these characteristics and the further selection and cultivation of strains with these traits would be highly beneficial for the long-term technology development of algal cultivation in wastewater. Also, several authors have reported on the beneficial effects from microalgae-bacteria (de Bashan et al 2004;Mouget et al 2006;Watanabe et al 2005) and microalgae-fungi (Cheirsilp et al 2011;Shu et al 2013;Watanabe et al 2005) co-cultivation strategies. Such partnerships may have mutualistic or even symbiotic relationships (Watanabe et al 2005) in which the algal Bpartners^generate carbon dioxide and consume oxygen in situ (Adlercreutz et al 1982;Mouget et al 2006), supply essential vitamins (Croft et al 2006;Kazamia et al 2012), increase bioavailability of micronutrients (e.g., iron) (Amin et al 2009), and defend against competitors (Evens et al 2011) to impact overall algal cell development (Matsuo 2005) and metabolic profiles (Paul et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The elucidation of these characteristics and the further selection and cultivation of strains with these traits would be highly beneficial for the long-term technology development of algal cultivation in wastewater. Also, several authors have reported on the beneficial effects from microalgae-bacteria (de Bashan et al 2004;Mouget et al 2006;Watanabe et al 2005) and microalgae-fungi (Cheirsilp et al 2011;Shu et al 2013;Watanabe et al 2005) co-cultivation strategies. Such partnerships may have mutualistic or even symbiotic relationships (Watanabe et al 2005) in which the algal Bpartners^generate carbon dioxide and consume oxygen in situ (Adlercreutz et al 1982;Mouget et al 2006), supply essential vitamins (Croft et al 2006;Kazamia et al 2012), increase bioavailability of micronutrients (e.g., iron) (Amin et al 2009), and defend against competitors (Evens et al 2011) to impact overall algal cell development (Matsuo 2005) and metabolic profiles (Paul et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The main strategy to boost low CO 2 concentrations in algal cultures is to use CO 2 -enriched gases, but additional supply of CO 2 comes with a significant cost (Clarens et al, 2010). Bacterial degradation of organic compounds released by algae contributes an additional source of CO 2 for algal growth, especially during CO 2 -limiting conditions as this CO 2 can be fixed again by algae (Mouget et al, 1995;Subashchandrabose et al, 2011). This is exemplified with the case of a Chlorella sp.…”
Section: Nutrient Provisionmentioning
confidence: 99%
“…The positive 'holobiont' correlations observed in P. tricornutum phycosphere enrichment #2 between algal 13 C incorporation and the 13 C incorporation of their attached bacteria implied that increased algal C fixation resulted in higher quantities of C transferred to their attached bacteria. It is possible that attached bacteria respired the algal C and relieved microscale CO 2 limitation in P. tricornutum (Mouget et al, 1995). This would have had the added effect of removing O 2 from the microenvironment, thus enhancing C fixation efficiency by reducing algal photorespiration (Molina et al, 2001).…”
Section: N Salina-interactions With Bacteria Dictated By Small Sizementioning
confidence: 99%